Errors In Writing Recount Text Made By The Eighth Grade Students Of SMP N 2 Ngemplak Boyolali In 2015 / 2016 Academic Year - PRASETYOWATI, YUNIA DWI; , Prof.Dr.Endang Fauziati, M.Hum; , Aryati Prasetyarini, S.Pd., M.Pd (2016)
Yunia Dwi Prasetyowati. A320120099. ERRORS IN WRITING RECOUNT TEXT MADE BY THE EIGHTH GRADE STUDENTS OF SMP N 2 NGEMPLAK BOYOLALI IN 2015/2016 ACADEMIC YEAR. Research Paper. Teacher Training and Education, Muhammadiyah University of Surakarta. May, 2016. The aims of this research are to identify the types of errors made by the eighth grade students of SMP N 2 Ngemplak Boyolali in their writing recount text, especially to identify the types of lexical, syntactical, and discourse errors. It is also to find out the frequency of each type of errors, dominant type of errors, and the sources of errors. The type of this research is descriptive qualitative research. In collecting the data, the writer uses elicitation. It consists of four steps; the writer gives explanation about recount text, orders to the students to make recount text with the topic given, the writer reads and marks the types of errors in the students writing composition, writes the erroneous sentences and classifies all types of error based on linguistic category and surface strategy taxonomy. The technique for analyzing data consists of six steps, namely identification of errors, classifying into error types, describing the frequency of error, describing the dominant type of error, analyzing of the sources of error, and describing the proposed remedial teaching. The result of the study shows that lexical errors amounts to 15,51 % that consist of False friend (similar in meaning), False friend (similar in form), Wrong spelling, and Code switching. Syntactical errors amounts to 79,08 % which consists of Verb (addition of verb, misuses of verb in past tense, addition of to in present tense), Noun (omission of -s in plural marker, omission of possessive adjective, addition of -s in plural marker), BE (omission of BE, addition of BE in past tense, misuses of BE), Pronoun (omission of -s in possessive pronoun ), Phrase (misordering (noun phrase), Article (omission of article the, omission of article a , x addition of article the), Preposition (omission of preposition, addition of preposition, misuses of preposition ), Conjunction (omission of conjuction), Sentence Construction (omission had as predicate , omission of subject). Discourse errors are 5,36 % that consists of generic structure and conjuction. The dominant type of errors is misuse of verb in past tense. The writer also finds two sources of errors, namely interlingual transfer and intralingual transfer. Keywords: Error Analysis, Recount Text, Linguistic Category Taxonomy, Surface Strategy Taxonomy, Source of Errors.